Whose negative emissions? Exploring emergent perspectives on CDR from the EU's hard to abate and fossil industries - Brad, Alina; Haas, Tobias; Schneider, Etienne (Frontiers in Climate, 2024)
Net zero targets have rapidly become the guiding principle of climate policy, implying the use of carbon dioxide removal (CDR) to compensate for residual emissions. At the same time, the extent of (future) residual emissions and their distribution between economic sectors and activities has so far received little attention from a social science perspective. This constitutes a research gap as the distribution of residual emissions and corresponding amounts of required CDR is likely to become highly contested in the political economy of low-carbon transformation. Here, we investigate what function CDR performs from the perspective of sectors considered to account for a large proportion of future residual emissions (cement, steel, chemicals, aviation) as well as the oil and gas industry in the EU. We also explore whether they claim residual emissions to be compensated for outside of the sector, whether they quantify these claims and how they justify them. Relying on interpretative and qualitative analysis, we use decarbonization or net zero roadmaps published by the major sector-level European trade associations as well as their statements and public consultation submissions in reaction to policy initiatives by the EU to mobilize CDR. Our findings indicate that while CDR technologies perform an important abstract function for reaching net zero in the roadmaps, the extent of residual emissions and responsibilities for delivering corresponding levels of negative emissions remain largely unspecified. This risks eliding pending distributional conflicts over residual emissions which may intersect with conflicts over diverging technological transition pathways advocated by the associations.